2011
DOI: 10.1152/ajprenal.00552.2010
|View full text |Cite
|
Sign up to set email alerts
|

Rare mutations in the human Na-K-Cl cotransporter (NKCC2) associated with lower blood pressure exhibit impaired processing and transport function

Abstract: The Na-K-Cl cotransporter (NKCC2) is the major salt transport pathway in the thick ascending limb of Henle's loop and is part of the molecular mechanism for blood pressure regulation. Recent screening of ∼3,000 members of the Framingham Heart Study identified nine rare independent mutations in the gene encoding NKCC2 (SLC12A1) associated with clinically reduced blood pressure and protection from hypertension (Ji WZ, Foo JN, O'Roak BJ, Zhao H, Larson MG, Simon DB, Newton-Cheh C, State M, Levy D, Lifton RP. Nat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 29 publications
(48 reference statements)
4
30
1
Order By: Relevance
“…One emerging and promising strategy for the possible treatment of ERAD diseases is to overcome ER retention (61,62,64) because some mutant proteins such as the cystic fibrosis ⌬F508-CFTR mutant are actually functional if they exit the ER and reach their normal cellular location (63,65). In regard to NKCC2, previous reports demonstrated that, when expressed in a mammalian cell background, several NKCC2 mutants are retained in the ER (10,25,66). Moreover, although distinct cellular mechanisms may account for NKCC2 loss of function in BS1 disease, our preliminary data in the laboratory revealed that ER-associated protein degradation is the most common mechanism underpinning BS1.…”
Section: Discussionmentioning
confidence: 99%
“…One emerging and promising strategy for the possible treatment of ERAD diseases is to overcome ER retention (61,62,64) because some mutant proteins such as the cystic fibrosis ⌬F508-CFTR mutant are actually functional if they exit the ER and reach their normal cellular location (63,65). In regard to NKCC2, previous reports demonstrated that, when expressed in a mammalian cell background, several NKCC2 mutants are retained in the ER (10,25,66). Moreover, although distinct cellular mechanisms may account for NKCC2 loss of function in BS1 disease, our preliminary data in the laboratory revealed that ER-associated protein degradation is the most common mechanism underpinning BS1.…”
Section: Discussionmentioning
confidence: 99%
“…86 Rb ϩ Influx Assays-NKCC function was assessed by measuring 86 Rb ϩ influx into HEK cells in a 96-well plate as described previously (3,10,22), using an automated 96-well assay flux machine. To optimize cell surface expression (6), cells were grown to confluence in 96-well polylysine-coated plates and moved to a 25°C incubator 24 h prior to the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…To optimize cell surface expression (6), cells were grown to confluence in 96-well polylysine-coated plates and moved to a 25°C incubator 24 h prior to the experiment. To activate NKCC1, cells were exposed to a low chloride hypotonic medium for 45 min (3,22); in the experiments of Fig. 3 Results are presented as mean Ϯ S.E.…”
Section: Methodsmentioning
confidence: 99%
“…For example, reduced temperature rescues both wild type and mutant forms of immature CFTR, resulting in increased steady state CFTR abundance, enhanced ER export, and delivery to the cell surface (35). A recent study found that incubation of cells at 25°C also increased wild type NKCC2 protein abundance, indicating that, like CFTR, members of the cation chloride cotransporter family are processed in a temperature-sensitive manner (35,36). Current evidence suggests that altered client-chaperone interactions are partly responsible for the beneficial effect of low temperature on protein biogenesis (37).…”
Section: Bandmentioning
confidence: 99%